Use of platelet concentrates in oral and maxillofacial surgery: an overview. (2nd January 2017) - Mihaylova, Zornitsa; Mitev, Vanyo; Stanimirov, Pavel; Isaeva, Antonia; Gateva, Natalia; Ishkitiev, Nikolay
Abstract: Objective: To describe and provide a comprehensive overview on the development, use and efficacy of autologous platelet concentrates in different in vitro and in vivo studies focusing on oral and maxillofacial pathologies. Materials and methods: Present work employs an extensive critical overview of the literature on the development and application of platelet concentrates. Results: Platelet concentrates are innovative endogenous therapeutic agents which gained a lot of interest in different medical and dental disciplines due to their potential ability to stimulate and increase regeneration of soft and hard tissues. The effect of platelet-derived products is considered to be a result of the high number of platelets which contain a wide range of growth factors. They are not just therapeutic products but autologous blood concentrates containing active molecules. The quality of platelet concentrates may vary according to the individual physical state of donors making it difficult to to compare the outcomes of their application. Although, there are many studies analyzing the properties of these biomaterials both in vivo and in vitro, a consensus regarding their efficacy still has to be reached. Conclusion: Evidences described in the literature on the efficacy of platelet concentrates in procedures in oral and maxillofacial region are controversial and limited. In order to clarify the real advantages and priorities for the patients, when the blood-derived products are applied, further in vitro and in vivo research about the activity of PRP and PRF on the dental cells biology should be conducted.